Ongoing Remote Work, Returning to Working at Work, or in between during COVID-19: What Promotes Subjective Well-Being?. (March 2023) - Fan, Wen; Moen, Phyllis
The COVID-19 pandemic precipitated a massive turn to remote work, followed by subsequent shifts for many into hybrid or fully returning to the office. To understand the patterned dynamics of subjective well-being associated with shifting places of work, we conducted a nationally representative panel survey (October 2020 and April 2021) of U.S. employees who worked remotely at some point since the pandemic (N = 1, 817). Cluster analysis identified four patterned constellations of well-being based on burnout, work–life conflict, and job and life satisfaction. A total return to office is generally more stressful, leading to significantly lower probabilities of being in the optimal low stress/high satisfaction constellation by Wave 2, especially for men and women without care obligations. Remote and hybrid arrangements have salutary effects; moving to hybrid is especially positive for minority men and less educated men, although it disadvantages White women's well-being.